2016
DOI: 10.1111/ctr.12746
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative antimicrobials after lung transplantation and the development of multidrug‐resistant bacterial and Clostridium difficile infections: an analysis of 500 non‐cystic fibrosis lung transplant patients

Abstract: One-third (34%) of non-CF lung transplants develop MDR infections and 6% develop CDI within 90 d of postoperative antimicrobials. The duration of Gram-positive antimicrobials may increase the risk of MDR/CDI, while early transfer from the ICU may have a protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…The right balance to prevent infection risk with limited side effects is not known. The duration of gram-positive antimicrobials has been described to increase the risk of MDR and Clostridioides difficile infection in an analysis of 500 non-cystic fibrosis lung transplant patients [10]. In our survey, some centers adapted and stopped antibiotic therapy as soon as possible if the results of the bacteriological screening in donor and recipient were negative and there was no sign of infection.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The right balance to prevent infection risk with limited side effects is not known. The duration of gram-positive antimicrobials has been described to increase the risk of MDR and Clostridioides difficile infection in an analysis of 500 non-cystic fibrosis lung transplant patients [10]. In our survey, some centers adapted and stopped antibiotic therapy as soon as possible if the results of the bacteriological screening in donor and recipient were negative and there was no sign of infection.…”
Section: Discussionmentioning
confidence: 94%
“…We observed different antibiotic strategies between non-colonization recipients and recipients colonized with MDR bacteria in our survey, even under similar clinical conditions. Indeed, the presence of MDR bacteria followed the direction of the highest "caution" and, as an example, longer antibiotic therapy and less de-escalation were the reported responses despite a well-known risk factor for multidrug-resistant (MDR) bacterial and Clostridioides difficile infections in longer therapy [10][11][12]. It is still debated whether MDR bacteria are more problematic than wild-type agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in lung transplant recipients have demonstrated increased incidence of MDROs and Clostridioides difficile due to longer courses of broad-spectrum antibiotics. 21,22 One study noted 34% of non-Cystic Fibrosis lung transplant recipients developed an MDRO infection and 6% developed Clostridioides difficile infection within 90 days of postoperative antibiotics. 21 The benefits of prolonged duration of perioperative antibiotics should be weighed against these additional risks.…”
Section: Discussionmentioning
confidence: 99%
“…Infekce Clostridium difficile je častou komplikací v čas ném období po LuTx při imunosupresivní léčbě a potrans plantační antibiotické profylaxi a postihuje až 6 % příjemců v prvních 90 dnech po LuTx [42].…”
Section: Tuberkulózaunclassified